Some aspects of bush encroachment in the African rangelands - Bille, Jean-Claude (Australian Academy of Science, 1985)
Describes the woody components in the African Savanna rangelands and the production of wood and grass with supporting data on number of trees & shrubs per hactare (Data from Ethiopia and Senegal); also describes the tree populations with data on woody layer and grass layer productivities in various climatic conditions of tropical Africa and tree population at two sites in Upper Volta.